Morphological, biochemical and genetic variation of rice (Oryza sativa L.) genotypes to vegetative stage salinity stress - Che Yah, Fatien Najwa; Shamsudin, Noraziyah Abd Aziz; Ab Razak, Mohd Shahril Firdaus; Yusop, Mohd Rafii; Bhuiyan, Md Atiqur Rahman; Nordin, Mohd Shukor (Horizon e-Publishing Group, 2023)
Salinity is one of the most serious issues in rice cultivation and production. Salt stress significantly reduced seedling growth performance of rice. This research was conducted to study the effects of vegetative stage salinity stress on morphological, biochemical, molecular and genetic variation of 12 rice genotypes including 2 check varieties, MR297 (susceptible) and Pokkali (tolerant). The experiment was arranged in a split-plot design with 3 replications. Normal freshwater at 0 dS m-1 (L1), saline water at 6 dS m-1 (L2) and saline water at 12 dS m-1 (L3) were the main plot and rice genotypes were the sub-plot. In general, morphological and biochemical traits of all genotypes showed an overall reduction of about 47.41 in L3 as compared to L1 except for the tolerant check, Pokkali. The genetics and correlation analysis indicated that plant height, leaf size and standard evaluation system (SES) score might be used as a selection criterion in developing salt tolerant rice. The multivariate analysis revealed that a Malaysian landraces, Jarom Mas was clustered together with Pokkali as tolerant genotype. Screening using tightly linked Simple Sequence Repeat (SSR) markers (RM1287, RM10748, RM493) of salinity tolerant QTL, Saltol indicated that this QTL was absence in Jarom Mas. This finding might indicate the presence of other QTL associated with salinity tolerance in Jarom Mas. Further study on identifying the speculated QTL may be conducted to confirm this postulation.